(untitled) (IUBAT Review, 2024)
The experiments were carried out at Plant Pathology Department, Bangladesh Jute Research Institute (BJRI), Dhaka, Bangladesh. Fifteen Seed samples of 10 varieties of Corchorus capsularis collected from seven research stations (Kishorganj, Comilla, Jessore, Potuakhali, Manikganj, Dinajpur and Rangpur) of BJRI for evaluating the quality of seeds, where1000-seed weight/sample ranged from 3.05 to 3.67g, the lowest and highest weights were recorded in CVL–1 of Comilla and in Breeder Seed of CVL-1of Manikganj. Highest pure seed (96.40%) recorded in CVL – 1 of Jessore and lowest (89.41%) in Breeder seed CVL – 1 of Manikganj. The Germination of collected seeds varied from 56 to 88%, where the highest and lowest counts were made in CVL -1 of Rangpur and CVL – 1 of Jessore. The highest (21%) seed yielded fungi per sample of Breeder seed CVL -1 of Manikganj and lowest (6%) in Deshi pat -1 of Potuakhali. The highest ratio (7.3:1) between % seed germination and % seed germination failure found in CVL -1 of Rangpur and lowest ratio (1.2:1) in CVL - 1 of Jessore. Seed borne fungi viz. Macrophomina phaseolina, Botryodiplodia theobromae, Colletotrichum corchori, Aspergillus niger, Aspergillus flavus, and Penicillium Spp. were determined. IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 152-162